One-year follow-up after primary coronary intervention for acute myocardial infarction in diabetic patients: a substudy of the STENT PAMI trial - Mattos,Luiz Alberto (2001)
OBJECTIVE - This analysis was undertaken to determine the composite incidence of cumulative adverse events (death, reinfarction, disabling stroke, and target vessel revascularization) at the end of the first year after acute myocardial infarction, in diabetic patients who underwent coronary stenting or primary coronary balloon angioplasty. METHODS - From the STENT PAMI trial, we analyzed the 6-month angiographic and 1-year clinical outcomes of 135 diabetic (112, noninsulin dependent) patients who underwent the randomization process of the trial and compared them with 758 nondiabetic patients. RESULTS - Coronary stenting did not significantly reduce the primary composite clinical end point when compared with PTCA (20 vs. 30%, p=0.2). A significant benefit from stenting was observed in patients with noninsulin dependent diabetes, with a trend toward a lesser need for new revascularization procedures (10 vs. 21%, p<.001), with a significant reduction in the primary composite clinical end point at 1 year (12 vs. 28%, p=. 04). At 6 months, the restenosis rate were significantly reduced only in nondiabetic patients (18 vs. 33%, p<. 001). Diabetic patients had the same restenosis rate (38%) either with stenting or balloon PTCA. CONCLUSIONS - Coronary Stenting in diabetics noninsulin dependent offered a significant reduction in the composite incidence of major clinical adverse events compared with balloon PTCA.